Avatar : Fire and ash [videorecording (DVD)] - Franglen, Simon (20th Century Studios, 2026)
"In the most powerful chapter of the Avatar saga yet. As Jake and Neytiri guide their family through grief, they journey with the nomadic Wind Traders across Pandora's skies. But the Sullys' path is threatened by a new enemy -- the Ash People, a warlike clan led by the fierce Varang -- who have turned against Eywa and the ancient Na'vi way."--Disc container.